1993
DOI: 10.2527/1993.714930x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle histochemical and biochemical properties in relation to meat quality during selection for increased lean tissue growth rate in pigs1

Abstract: The relationship between the histochemical and biochemical properties of muscle and the quality of meat during selection to improving the lean tissue growth rate was studied. Pigs (n = 82) from Generations 2 and 4 were randomly sampled in a selection experiment in which the genotype x protein interaction was studied. Comparisons were made of longissimus muscle (LM) and quadriceps femoris (QF) from Generations 2 and 4, and biceps femoris (BF) in the fourth generation from pigs fed a low- or high-protein diet. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
81
5
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(106 citation statements)
references
References 19 publications
18
81
5
2
Order By: Relevance
“…Divergent selection for lean growth rate or efficiency of feed conversion can result in similar responses in carcass composition, but can have different effects on meat quality traits (Cameron et al, 1999). In contrast to ours, the increased ADG was not accompanied by changes in LMP in the studies of Karlsson et al (1993) and Oksbjerg et al (2000). In our study, higher ADG was associated with lower LMP, mainly due to a higher fat thickness.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Divergent selection for lean growth rate or efficiency of feed conversion can result in similar responses in carcass composition, but can have different effects on meat quality traits (Cameron et al, 1999). In contrast to ours, the increased ADG was not accompanied by changes in LMP in the studies of Karlsson et al (1993) and Oksbjerg et al (2000). In our study, higher ADG was associated with lower LMP, mainly due to a higher fat thickness.…”
Section: Discussioncontrasting
confidence: 99%
“…For instance, numerous studies have reported the positive effect of the halothane genotype on carcass lean content and conformation; however, this positive effect was often accompanied by a negative effect on meat quality traits (De Smet et al, 1995 andLeach et al, 1996). Also in other studies aiming at increasing lean tissue growth by selection or by feeding strategies, a decrease in meat quality was noticed (Karlsson et al, 1993;Oksbjerg et al, 2000). On the other hand, the IGF-2 mutation shows that selection for increased LMP does not have to have unfavourable effects on meat quality (Van den Maagdenberg et al, 2005 and unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in fibre types composition observed in present study between three different crossbreeds of fatteners appear similar to those reported earlier by Karlsson et al (1993) and Larzul et al (1997), in which authors have demonstrated that muscle fibre composition and size is specific for different pig breeds or lines. Ruusunen and Puolanne (1997) found that Pig muscles with many oxidative fibres tolerate stressful conditions better during transport, resulting in a slower fell in pH after slaughter.…”
Section: Resultssupporting
confidence: 79%
“…According to Essen-Gustavsson and Fjelkner-Modig (1985) muscle oxidative capacity affects meat quality by improving the sensory properties of meat. Moreover, evidence from the literature (Karlsson et al, 1993;Koch et al, 1995) indicates that muscle characteristics and particularly fibre type frequency may be an important source of variation in eating quality. However, the influence of fibre type on meat tenderness is not fully understood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation